OPERATING COST ANALYSIS: SOURCES AND METHODS (INNOVATIVE ECONOMY, 2020)
Khorunzhak N.M., Portovaras T.R. OPERATING COST ANALYSIS: SOURCES AND METHODSPurpose. The aim of the article is identification of requirements and composition of sources of analysis, critical assessment of their information content, as well as emphasis on the application of a systematic approach to the analysis of operating costs and compliance of its method with these criteria.Methodology of research. The empirical research methods are used in the course of the research, in particular: analysis – in order to identify the composition of sources of analysis of operating expenses; generalization – to substantiate the classification of sources of analysis and to formulate recommendations on the choice of methods of analysis, which most fully allow to estimate the operating costs.Findings. The principles of formation of information base of the analysis of operating expenses are substantiated, which will allow to obtain high-quality information on their status and on the basis of the obtained results to predict the activity of the enterprise in the future. The study of the impact of factors on the analysis of operating expenses allowed us to distinguish sources of information into two groups: internal and external. It is determined that internal sources of data for analysis are accounting records, which are formed at enterprises, and which is considered by the authors as a source of analysis of operating expenses. External sources of information the authors consider all possible information resources of an external nature, research of the competitive environment and reporting of subjects with similar types of activity.Originality. The scheme of interconnection sources and analysis results of operations is proposed, which comprehensive utilization, will allow obtaining result analytical information on which management can optimize the cost of compliance with objectives and increase effectiveness of operations.According to modern realities, the most suitable methods of analysis are offered, which allow to adequately assessing the situation of the enterprise in the strategic plane with respect to operating expenses.Practical value. Carrying out an assessment of the operating costs of an enterprise with using various methods and tools of analysis in a complex provides obtaining unbiased data that can be effectively used for the purpose of cost optimization and increase of productivity.Key words: analysis; operating costs; cost optimization; internal sources of information; external sources of information; strategic methods; ABC analysis.
Keywords: Key words; analysis; operating costs; cost optimization; internal sources of information; external sources of information; strategic methods; ABC analysis.